Vozes e memórias docentes: a trajetória entre a modalidade presencial e a educação a distância na percepção de professores de Instituições de Ensino Superior privadas do RS - Moroni, Alexandre (2015)
The theme of this project is the distance learning and the object is the career of teachers laboring in face-to-face graduation courses and started do work in graduation courses in EAD (Distance Education). The problem raised for research purposes formulates the question: how was the transition of teachers laboring with classroom teaching to the Distance Education mode? The main concepts and theories that based the construction of this project were in the issue of Social Memory: Halbwachs (2006), Gondar (2005) and Dodebei (2009); in the issue of Memorial: Axt (2012); and in the issue of Distance Education: Litto and Formiga (2009; 2012), Mattar (2011), Tori (2010), Belloni (2009), Moore, and Kearsley (2007). The aim of this project is to know, from the teachers memories with prior performance in classroom teaching in university education, how they felt changing to Distance Education courses. The research took place in two steps: with exploratory, through bibliographical and documentary research, 2013-2015; and field research through survey data from 2013 and thematic interviews from 2014. The data analysis was performed using the Thematic Content Analysis technique. This work presents as a final product the construction of a virtual space called MemorialEAD, which mission is to preserve the past, experience the present and assist in building the future of EAD in Brazil. In this virtual memory space, professors of University Education Institutions from Rio Grande do Sul can record their perceptions of the current EAD scenario as well as their memories. In MemorialEAD virtual space their presentation, mission and goals are presented; bibliographical and documentary research on the development of EAD in Brazil, photos of the evolution of distance learning and its technologies, legislation that deals with the EAD in Brazil, search sites from the Internet with credibility and list of articles, news, events, reports, statistics related to the EAD. It also has support tools for professors and tutorials of use and a VLE (Virtual Learning Environment) by offering free courses technologies in the education area. It should be highlighted that the MemorialEAD, besides being a digital repository of these teaching narratives, intends to carry out and disseminate new research related to Distance Education.